A young galaxy cluster in the old Universe. Issue 2 (12th August 2019) - Hashimoto, Tetsuya; Goto, Tomotsugu; Momose, Rieko; Ho, Chien-Chang; Makiya, Ryu; Chiang, Chia-Ying; Kim, Seong Jin
ABSTRACT: Galaxies evolve from a blue star-forming phase into a red quiescent one by quenching their star formation activity. In high-density environments, this galaxy evolution proceeds earlier and more efficiently. Therefore, local galaxy clusters are dominated by well-evolved red elliptical galaxies. The fraction of blue galaxies in clusters monotonically declines with decreasing redshift, i.e. the Butcher–Oemler effect. In the local Universe, observed blue fractions of massive clusters are as small as ≲0.2. Here we report a discovery of a 'blue cluster' that is a local galaxy cluster with an unprecedentedly high fraction of blue star-forming galaxies yet hosted by a massive dark matter halo. The blue fraction is 0.57, which is 4.0σ higher than those of the other comparison clusters under the same selection and identification criteria. The velocity dispersion of the member galaxies is 510 km s −1, which corresponds to a dark matter halo mass of 2.0^+1.9_-1.0× 10^14 M⊙ . The blue fraction of the cluster is more than 4.7σ beyond the standard theoretical predictions including semi-analytic models of galaxy formation. The probability to find such a high blue fraction in an individual cluster is only 0.003 per cent, which challenges the current standard frameworks of the galaxy formation and evolution in the ΛCDM universe. The spatial distribution of galaxies around the blue cluster suggests that filamentary cold gas streams can exist in massive haloes even in the local Universe. However these cold streams have already disappeared in the theoretically simulated local universes.